2016
DOI: 10.1186/s12943-016-0547-x
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: low expression of MT1-MMP is optimal to promote migration and tumourigenesis of breast cancer cells

Abstract: BackgroundMembrane Type-1 Matrix Metalloproteinase (MT1-MMP) is a multifunctional protease implicated in metastatic progression ostensibly due to its ability to degrade extracellular matrix (ECM) components and allow migration of cells through the basement membrane. Despite in vitro studies demonstrating this principle, this knowledge has not translated into the use of MMP inhibitors (MMPi) as effective cancer therapeutics, or been corroborated by evidence of in vivo ECM degradation mediated by MT1-MMP, sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 75 publications
4
47
0
Order By: Relevance
“…When tested for their ability to inhibit the gelatinolytic activity of MMP9, our MMP9-selective N-TIMP2 variants showed selective inhibition of MMP9 stably expressed by MCF-7-MMP9 cells. The same effect was observed in a different experimental system in which cell migration/mobility, previously shown to be dependent on the expression of MMP9 and MMP14, of MCF-7 cells stably expressing MMP9 was measured [ 77 , 79 ]. Inhibited mobility was caused by N-TIMP2 WT and the specific MMP9-inhibiting N-TIMP2 protein variants at 100 nM concentrations, whereas no inhibition was observed with any of the MMP14-specific N-TIMP2 variants.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…When tested for their ability to inhibit the gelatinolytic activity of MMP9, our MMP9-selective N-TIMP2 variants showed selective inhibition of MMP9 stably expressed by MCF-7-MMP9 cells. The same effect was observed in a different experimental system in which cell migration/mobility, previously shown to be dependent on the expression of MMP9 and MMP14, of MCF-7 cells stably expressing MMP9 was measured [ 77 , 79 ]. Inhibited mobility was caused by N-TIMP2 WT and the specific MMP9-inhibiting N-TIMP2 protein variants at 100 nM concentrations, whereas no inhibition was observed with any of the MMP14-specific N-TIMP2 variants.…”
Section: Discussionsupporting
confidence: 69%
“…Many cancer cell lines express both MMP14 and MMP9 [ 74 , 75 ]. To assess the specific effects of our selective inhibitors on each MMP, we utilized the MCF-7 breast cancer cell line that is naturally MMP14- and MMP9-deficient [ 76 , 77 ]. First, we stably transfected the cells with a full-length MMP9 construct to generate MCF-7-MMP9 cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Recent studies demonstrated that MMPs play fundamental roles in the migration and proliferation of tumor cells. 25 Additionally, high levels of MMP expression are associated with NPC development. Yang et al 26 reported that MMP2 and MMP9 promote NPC metastasis, and Hsu et al 27 showed that MMP9 enhances human NPC cell invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, MT1-MMP (membrane type-1 matrix metalloproteinase, MMP14) is a key protease that activates pro-MMPs such as MMP2 and MMP9 and is associated with ECM degradation and cell migration during cancer metastasis [33, 34]. Cepeda et al reported that optimal levels of active MT1-MMP required the elevated pERK levels in breast cancer [35]. Lin et al also showed that MT1-MMP mediated breast cancer invasion possibly through activating MAPK/ERK pathway [36].…”
Section: Discussionmentioning
confidence: 99%